Population Aging and Individual Attitudes toward Immigration: Disentangling Age, Cohort and Time Effects - Lena Calahorrano (Deutsches Institut für Wirtschaftsforschung (DIW), 2011)
In the face of rising old-age dependency ratios in industrialized countries like Germany, politicians and their electorates discuss the loosening of immigration policies as one policy option to ensure the sustainability of public social security systems. The question arises whether this policy option is feasible in aging countries: older individuals are typically found to be more averse to immigration. However, cross-sectional investigations may confound age with cohort effects. This investigation uses the 1999-2008 waves of the German Socio-Economic Panel to separate the effect of age on immigration attitudes from cohort and also from time effects. Over the life cycle stated immigration concerns are predicted to increase well into retirement and decrease afterward. Relative to other issues, immigration concerns are found to actually decrease over the life cycle.
Keywords: D78; F22; J10; 330; Immigration; demographic change; political economy; Einwanderung; Meinung; Lebensverlauf; Migrationspolitik; Alternde Bevölkerung; Deutschland